Avaliação nutricional de sojas integrais desativadas para leitões na fase de creche - Toledo, Juliana Beatriz (2009)
Two experiments were carried out to determine the nutritional value and to verify the piglets performance in starting phase (6 to 15 kg), fed with diets containing two types of disabled whole soybeans characterized by the shell presence (CS) or not (SS). In digestibility assay (Exp. I) were used 15 piglets male, castrated, with average weight of 7.36 ± 1.71 kg, housed in cages of metabolism, distributed in a randomized design with three treatments, five replicates, one pig each. The values of digestible energy (DE), as well the metabolizable energy (ME) on fed basis for SC and SS were: 3.979 and 4.300 kcal/kg, 3.768 and 4.111 kcal/kg, respectively. In the performance experiment (Exp. II) were used 56 piglets, weaned at 21 days of age with initial body weight of 6.19 ± 0.67 kg. The animals were distributed in a completely randomized design in a factorial 2 x 3 arrangement with two types of soybean (SC and SS) and three levels of inclusion (4,5; 9,0 and 13,5%), four replicates and two pigs per experimental unit. The experimental treatments were: a control diet (RC) based on corn and soybean meal, and other diets containing six inclusion levels of each of the two disable whole soybeans, totaling seven treatments. The animals were weighed at the beginning (6 kg) during (10 kg) and at the end (15 kg) of the trial. The first phase corresponded to the weight from 6 to 10 kg and from 6 to 15 kg for Total Phase. There were no differences in digestibility coefficients of DM, CP, EE, OM and in the metabolism coefficient of GE between the two soybean evaluated. However, there was difference in the GE digestibility, where the SS was superior to SC. In the performance assay, there was no interaction between type and level of soybean inclusion on variables CDR, CA and ADG of piglets in phases I (6 to 10 kg) and total phase (6 to 15 kg). No differences were observed for the variables of performance with the inclusion of increasing levels of SS and SC disabled soybeans in the diets, thus verifying that the levels can be used in piglets diets.